Soil Stabilization Using Slag Cement for Improved CBR Performance: A Study in Lebak Regency, Banten - Fathonah, Woelandari; Kusuma, Rama Indera; Mina, Enden; Negoro, Giant Muhammad Satrio; Abdurohim, Abdurohim (Jurnal Fondasi, 2023)
The site of Kukulu Village, Parungsari Village, Sajira District, Lebak Regency, Banten was examined in this study. The Dynamic Cone Penetrometer test indicated that the soil carrying capacity value in this location was rather low, at 3.8%. It is crucial to remember that excellent subgrade soil (basic soil) has to have a CBR value of at least 6%. The use of slag cement is good for stabilizing soil because it contains silica and is cementitious. Slag cement is an environmentally friendly material, therefore in this study slag cement was used. The Unified Soil Classification System (USCS) will be used in this study to define the soil type and classification. The soil's grain size, Atterberg limits, compaction, and laboratory CBR tests will all be examined in order to achieve this. The CBR value will be calculated for a period of time and at different percentages of 0%, 8%, 10%, and 12% before and after stabilization using slag cement. In previous research, it was carried out and obtained an optimum CBR value when adding 10% slag cement and experienced a decrease when adding 15% slag cement, so in this study we wanted to find out whether there was still an increase in the CBR value in the range of 10% to 15%. The results of the CBR test obtained the highest CBR value of 23% from the addition of 12% cement slag and 7 days of curing.